PENGARUH KOMPENSASI DAN KETERLIBATAN KERJA TERHADAP MOTIVASI KERJA PERAWAT DI RUMAH SAKIT PERMATA HATI DURI MANDAU KABUPATEN BENGKALIS - Zahri Iqbal; Nuryanti '; Ahmad Rifqi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to look at the effect of compensation and job involvement on nurses work motivation at Permata Hati Hospital Duri Mandau Bengkalis Region. The population in this study are 88 nurses in at Permata Hati Hospital Duri Mandau hospital. analytical technique is multiple linear regression with the work motivation as well as the dependent variable, compensation and job involvement as independent variables. From the analysis was found that the compensation received by nurses is good and accordance with the principles set out in compensation. Compensation significant effect on the motivation of the nurses working at Permata Hati Hospital Duri Mandau. The work involvement of nurses working at Permata Hati Hospital Duri Mandau is good so that nurses make the job as the center of their lives. Work Involvement significant effect on the motivation of the nurses working at Permata Hati Hospital Duri Mandau. Compensation and job involvement jointly significant effect on work motivation of nurses at Permata Hati Hospital Duri Mandau.Keyword : Work motivation, compensation and work involvement